Mobile Communication and its Adverse Effects - Dahal, Kul Prasad (Himalayan Physics, 2013)
Mobile phone became almost essential part of daily life for all generation of people. It functions with the help of transmission of electromagnetic waves from towers to the cell phones in the micro wave frequency region. The energy carried by the waves is not only useful for mobile communication but also produce adverse affects on the users' health as well as to all living beings which are in the radiation area. The paper aims to discuss some of the possible dark side of health concern by the usage of cell phone and radiation from the towers. It also aims to suggest the possible remedies to minimize the health problems. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 51-59 Uploaded date: 12/23/2013